2022
DOI: 10.1016/s2468-2667(22)00010-x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness evaluation of digital contact tracing for COVID-19 in New South Wales, Australia

Abstract: Background Digital proximity tracing apps were rolled out early in the COVID-19 pandemic in many countries to complement conventional contact tracing. Empirical evidence about their benefits for pandemic response remains scarce. We evaluated the effectiveness and usefulness of COVIDSafe, Australia's national smartphone-based proximity tracing app for COVID-19. Methods In this prospective study, done in New South Wales (NSW), Australia, we included all individuals in the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
92
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(95 citation statements)
references
References 24 publications
3
92
0
Order By: Relevance
“…Therefore, conventional contact tracing was extraordinarily effective, with more than 40 close contacts identified per COVID-19 case on average. 4 This is in sharp contrast with the fewer than two close contacts per case identified by conventional contact tracing in the UK study. 5 The contact tracing authorities in NSW were never overwhelmed during the study period and, therefore, the relative interest and the cost–benefit balance of digital contact tracing were probably less apparent than in other countries.…”
mentioning
confidence: 67%
See 2 more Smart Citations
“…Therefore, conventional contact tracing was extraordinarily effective, with more than 40 close contacts identified per COVID-19 case on average. 4 This is in sharp contrast with the fewer than two close contacts per case identified by conventional contact tracing in the UK study. 5 The contact tracing authorities in NSW were never overwhelmed during the study period and, therefore, the relative interest and the cost–benefit balance of digital contact tracing were probably less apparent than in other countries.…”
mentioning
confidence: 67%
“…In The Lancet Public Health , Florian Vogt and colleagues 4 report the findings from a prospective study of the deployment of COVIDSafe, Australia's national COVID-19 tracing app, in the state of New South Wales (NSW). The app was based on a centralised approach, in which the information of contacts is uploaded to a common database and accessed by public health authorities for risk assessment and notification.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that the extent of active usage of mobile contact tracing apps has a large impact on their effectiveness 18 , 19 . The time to notification of exposed contacts also plays an integral role for SARS-CoV-2 20 ; this is corroborated by our results regarding the contrasting reduction in R * based on whether a user inputs their positive result from an LFT or from a PCR test (where the PCR test involves a delay between the test date and the positive test result).…”
Section: Discussionmentioning
confidence: 99%
“…Digital contact tracing can augment an existing contact tracing system ( Plank et al, 2020 ) but this presupposes good integration with the existing tracing infrastructure ( Lee & Kim, 2021 ) and rapid response once a contact has been identified. There are circumstances in which digital tracing has not proved helpful ( Vogt et al, 2022 ) however.…”
Section: Introductionmentioning
confidence: 99%